The Influence of Sharia Values on Sustainability Interest in Partnering in Sharia MLM - Abdul Ghoni; Muhammad Sofwan Jauhari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to formulate a comprehensive Sharia-based construction of multi-level marketing (MLM) systems grounded in halal products within the framework of Islamic economic law. Triggered by the rapid growth of the global halal economy and the massive expansion of MLM in Indonesia, the research responds to the tension between strong normative guidelines especially DSN-MUI Fatwa No. 75/DSN-MUI/VII/2009 on Sharia tiered direct selling and the frequent emergence of money game–like practices under Sharia labels. Using a qualitative normative-juridical approach and library research, this study analyzes primary sources (Qur’an, hadith, fiqh muamalah, DSN-MUI fatwa, and Indonesian MLM regulations) and secondary empirical studies on Sharia MLM cases such as PayTren, K-LINK Syariah, and Tiens Syariah. The analysis proceeds through normative-descriptive mapping of Sharia principles, structural comparison between the PLBS framework and actual MLM designs, critical assessment using usul al-fiqh and maqasid al-shariah, and constructive model building. The findings show, first, that DSN-MUI Fatwa No. 75/2009 already provides a robust normative framework that centers on real halal products, sales-based commissions, prohibition of pyramid schemes, price fairness, and ethical marketing. Second, there is a consistent gap between this framework and field practice: compensation systems still allow significant passive income for uplines without proportional sales effort, recruitment narratives overshadow genuine product distribution, and pricing and promotion patterns often verge on gharar, maysir, riba, and zulm. Third, empirical evidence indicates that substantive implementation of Sharia principles positively affects MLM performance, suggesting that rigorous compliance is commercially viable. The study concludes by proposing that a Sharia-compliant MLM system based on halal products must integrate three inseparable dimensions: a clear fiqh- and fatwa-based normative foundation, detailed operational design of network and compensation structures that structurally minimize exploitation, and effective governance and supervision to ensure ethical consistency at distributor level. This integrated construction is expected to serve as a normative and practical reference for regulators, Sharia boards, and halal-based MLM entrepreneurs